(untitled) (Journal of Engineering, 2020)
The electrocoagulation process became one of the most important technologies used for water treatment processes in the last few years. It’s the preferred method to remove suspended solids and heavy metals from water for treating drinking water and wastewater from textile, diary, and electroplating factories. This research aims to study the effect of using the electrocoagulation process with aluminum electrodes on the removal efficiency of suspended solids and turbidity presented in raw water and optimizing by the response surface methodology (RSM). The most important variables studied in this research included electrode spacing, the applied voltage, and the operating time of the electrocoagulation process. The samples were taken from the Al Qadisiyiah water treatment plant. The treatment set up was in a batch mode; two parallel plates of aluminum were used as electrodes. Experimental results showed that the maximum removal efficiency of 96% for turbidity and 97% for TSS were obtained at operating time 60 minutes, voltage 30 V, and electrode spacing 1.7cm. Two models for predicting removal efficiency obtained, the first model was for turbidity with a correction factor of 94.7%, and the second one was for the TSS with a correction factor of 94.85%.